Socialsekreterares attityder till AI: En kvantitativ studie gällande AI inom socialtjänsten - Andersson,Moa; Avdic,Ajla (2026)
The purpose of this study is to explore social workers' attitudes towards AI as an assistive tool and attitudes towards how AI affects the work environment. We have conducted a quantitative study by sending a survey to the social services of the municipalities of Scania, Sweden. Social workers have answered questions regarding how AI affects the work environment and general questions about how AI affects or would affect their work. The results show that social workers have a predominantly positive attitude towards the development of AI in social services, to which education and training in AI contribute; however, they do not believe that AI can lead to legally sound decisions. Comments in the survey indicate concerns regarding confidential information and how AI tools can contribute to a breach in client confidentiality. We discuss the dilemma of perceived usefulness and perceived ease of use in contrast to discretion. Furthermore, we highlight the need for further research into social workers' attitudes towards AI, after AI has been widely implemented within social services.
Keywords: AI; Artificial Intelligence; social work; attitudes; work environment; Technology Acceptance Model